Recent developments in MrBUMP: better search‐model preparation, graphical interaction with search models, and solution improvement and assessment. Issue 3 (5th April 2018) - Keegan, Ronan M.; McNicholas, Stuart J.; Thomas, Jens M. H.; Simpkin, Adam J.; Simkovic, Felix; Uski, Ville; Ballard, Charles C.; Winn, Martyn D.; Wilson, Keith S.; Rigden, Daniel J.
Abstract : New developments in the MrBUMP pipeline, including graphical interaction with search models using CCP 4 mg and the use of ensemble search models, are reported. Abstract : Increasing sophistication in molecular‐replacement (MR) software and the rapid expansion of the PDB in recent years have allowed the technique to become the dominant method for determining the phases of a target structure in macromolecular X‐ray crystallography. In addition, improvements in bioinformatic techniques for finding suitable homologous structures for use as MR search models, combined with developments in refinement and model‐building techniques, have pushed the applicability of MR to lower sequence identities and made weak MR solutions more amenable to refinement and improvement. MrBUMP is a CCP 4 pipeline which automates all stages of the MR procedure. Its scope covers everything from the sourcing and preparation of suitable search models right through to rebuilding of the positioned search model. Recent improvements to the pipeline include the adoption of more sensitive bioinformatic tools for sourcing search models, enhanced model‐preparation techniques including better ensembling of homologues, and the use of phase improvement and model building on the resulting solution. The pipeline has also been deployed as an online service through CCP 4 online, which allows its users to exploit large bioinformatic databases and coarse‐grained parallelism to speed up the determination of a possible solution. Finally, the molecular‐graphics application CCP 4 mg has been combined with MrBUMP to provide an interactive visual aid to the user during the process of selecting and manipulating search models for use in MR. Here, these developments in MrBUMP are described with a case study to explore how some of the enhancements to the pipeline and to CCP 4 mg can help to solve a difficult case.